The solar noise barrier project 4: Modeling of full-scale luminescent solar concentrator noise barrier panels - Bognár, Ádám; Kusnadi, Suryadi; Slooff, Lenneke H.; Tzikas, Chris; Loonen, Roel C.G.M.; de Jong, Minne M.; Hensen, Jan L.M.; Debije, Michael G. (Renewable energy, 2020)
A full-size (1 × 5 m2) luminescent solar concentrator (LSC) has been constructed and the edge electric outputs from the attached photovoltaic cells monitored for a period of slightly over one year in the solar noise barrier (SONOB) “living lab” outdoor environment. The results of the edge electric output measurements were compared to ray-tracing simulations, revealing imperfections in the system design and production that resulted in the significantly reduced performance of the panel compared to expectations. Results of these calculations suggest edge emission improvements of a factor of 6–9 are possible: at these improved edge outputs, the LSC becomes a viable solar energy generator for the built environment, with significant visual appeal. A grey-box computer model has been developed to predict LSC performance using a realistic device design with reduced internal light scattering and better photovoltaic cell positioning. A second model is used for extrapolation of the LSC solar barrier electric performance with different orientations in different world locations. •Large luminescent solar concentrator (LSC) noise barrier performance simulated.•Apparent fluorescence yield demonstrator device much reduced compared to smaller devices.•Performance improvement > 6–9x predicted for large devices: would become commercially viable.•Improved predictive power for performance of the LSCs for any location given information of the illumination conditions.